Politics and Resistance Among Communist Women in Mandatory Palestine (IYUNIM: Multidisciplinary Studies in Israeli and Modern Jewish Society, 2026)
In this article, I examined the experiences of communist women in mandatory Palestine, women who were the flesh and blood of the Palestinian Communist Party (PCP), and how they dealt with the oppression mechanisms of British rule in the Land of Israel: from surveillance and arrest, through legal proceedings, to their everyday lives in internment facilities. Through this focus I suggest two complementary processes: the first – the placement of women in the history of the Palestinian Communist Party at the center of historic debate; and the other – a reexamination of the role of the lawyers who represented female communist prisoners, in order to better understand the relationship between law, ideology, and gender.Historic research has explored extensively the activity of these lawyers within Zionist contexts, however, their involvement in the communist arena remains marginalized. Therefore, I seek to broaden the boundaries of historiographic debate about the PCP, thus filling this great void in the research while offering a renewed reading of the communist arena as a place wherein gender identities were shaped in their interaction with legal and colonial mechanisms of power.I rely on a Marxist Feminist approach, theories of female resistance, and research methods that deal with interment spaces. These approaches enable the analysis of mechanisms of exclusion, agency, and resistance, and position internment and legal struggle as parts of shaping political subjectivity. My study is based on archival resources, autobiographic literature, and journalism of that period.
Keywords: Mandatory Palestine; Social History; Female Resistance; Political Internment; Gender and Law; Communist Women; Female Agency; Lawyers; Marxist Feminism; the PCP